Literary Genres in Daily Newspaper Politika - Biševac, Nemanja D. (Collection of Papers of the Faculty of Philosophy in Priština, 2019)
This paper presents the analysis of literary genres in the daily newspaper Politika. After minutely monitoring presentations of literary genres in dailies, we gain insight into the place they occupy in the journalistic style. After a detailed analysis of 28 issues published in February 2018, it is concluded that essays, poems, and book reviews are the most frequent genres. Bearing in mind that 131 articles with literary content or form were recorded in total, it can certainly be said that Politika emphasizes literature in journalism.